Dua Sisi Gelap Covid-19 : Dilematis Antara Keterbukaan Data Identitas Penderita Covid-19 Dan Transparansi Data Publik Dalam Rangka Menekan Stigmatisasi : Perspektif Dari Segi Sosiologi - Firmansyah, Yohanes; Haryanto, Imam (Metta : Jurnal Ilmu Multidisiplin, 2021)
The Covid-19 case has had a huge influence on all aspects of human life, starting from health, economy, sosial, law, and many more. The COVID-19 pandemic has caused various frictions between various interests, one of which is a clash between individual interests and community interests. One of the obvious things about this problem is regarding the impact of COVID-19 in the field of sociology, especially the relationship between individuals, especially the issue of community stigmatization regarding infectious diseases, the dilemma between the privacy rights of the identity of COVID-19 patients and the disclosure of publik data on COVID-19 patients with various risks will injure and cause multiple material and immaterial losses. On the other hand, Covid-19 also raises various sosial-psychological problems and legal problems that still do not regulate all aspects of human life. This paper describes the sociological elements of COVID-19, the right to privacy, publik information disclosure, and the sosial-psychological impact of COVID-19, along with a juridical review of the right to privacy and publik disclosure of information regarding the transparency of COVID-19.